Aeromechanics of the local zone of influence of a gas infrared emitter; Thermophysics and Aeromechanics; Vol. 31, iss. 3 - Borisov B. V. Boris Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Salagaev S. O. Semyon Olegovich; Salikhov F. Yu. Feliks Yurjevich (2024, 2024)
Title screen